Refugee representation in Malaysia: A study of media representations and personal narratives / Charity Lee Chin Ai - Charity , Lee Chin Ai (2016)

(untitled)
This study explores the representation of refugees living in Malaysia from two perspectives. Firstly, this study analysed representations of refugees in Malaysian media discourse by the significant Other in Malaysia, namely elite political voices and the Malaysian press. Secondly, the perspective of the refugee or the Self was explored through narrative analysis of refugee in-depth interviews. The analysis of the media texts revealed representations of the refugee along two binaries. First, the refugee as either an illegal immigrant or a recognised refugee. Second, the refugee as a social, political and security threat or a victim. The government voices frequently represented refugees negatively to legitimise keeping them out or managed as illegals. The alternative voices represented refugees as victims to foreground the government’s violation of international law and human rights. Three common identity themes emerged from the thematic analysis of refugee narratives: the refugee as homo sacer (the bare life), victim and the idealised Self. The refugee narratives were filled with stories that highlighted their victimisation and helplessness as they embraced, resisted or re-represented the existing representations assigned to them by the elite voices. Positioning analysis on the narratives of long-term refugees revealed that representations of refugees in wider discourse often left them with little room to negotiate a sense of Self despite living in Malaysia like a Malaysian. Despite feeling a sense of belonging to Malaysia, they struggled to manage problematic situations involving the local people and authorities because of particular identity claims they had to take up either by choice or out of necessity. This study hopes to provide insight into the complexity in representing refugees as well as to give refugees a space for actively responding to representations that involve them. Through iv future work from this study, it is hoped that a wider audience will come to understand how disempowering discourses and simplistic representations of refugees can often have damaging and long-lasting effects on the daily lives of this vulnerable group.